2015
DOI: 10.1159/000368516
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Folic Acid Supplementation on Renal Phenotype and Epigenotype in Early Weanling Intrauterine Growth Retarded Rats

Abstract: Background/Aims: The objective of this study was to examine the responses of p53 promoter methylation involved in kidney structure and function of early weaning intrauterine growth retarded (IUGR) rats to dietary folic acid supplementation. Method: Sprague-Dawley rats were fed isocaloric diets containing either 21% protein diet (normal feed) or 10% protein diet throughout pregnancy and normal feed during lactation. After weaning, Offspring were then fed onto normal feed and normal feed supplemented with 5 mg f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
1
9
0
1
Order By: Relevance
“…It is generally accepted that apoptosis leads to renal dysfunction subsequent to ischemia in DM [42-45]. Bcl-2 is a pivotal factor that determines whether or not apoptosis occurs in cells exposed to injury, and increasing expression of Bcl-2 can promote cell survival [46-50]. A previous study shows that enhancement of the Nrf2/HO-1 pathway played an anti-apoptosis role, and that activation of Nrf2 could induce the expression of HO-1 to enhance the expression of Bcl-2 [51].…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that apoptosis leads to renal dysfunction subsequent to ischemia in DM [42-45]. Bcl-2 is a pivotal factor that determines whether or not apoptosis occurs in cells exposed to injury, and increasing expression of Bcl-2 can promote cell survival [46-50]. A previous study shows that enhancement of the Nrf2/HO-1 pathway played an anti-apoptosis role, and that activation of Nrf2 could induce the expression of HO-1 to enhance the expression of Bcl-2 [51].…”
Section: Discussionmentioning
confidence: 99%
“…The pregnant rats in the LA group were fed protein-restricted feed during pregnancy, and normal feed and water supplemented with L-Arg 200 mg/kg/day during lactation. At weaning on postnatal day 21, the offspring of the three groups were all given normal feed and normal water for 8 weeks; this time period was specifically selected to represent the juvenile-pubertal period (16). The animals were housed in a room with temperature of 21-22˚C, humidity of 50-70% and a 12 h light/dark cycle.…”
Section: Methodsmentioning
confidence: 99%
“…Bcl-2 is a key protein that controls apoptosis in cells, and upregulation of Bcl-2 expression encourage cell survival (Liang et al, 2013;He et al, 2015;Sun et al, 2015;Wang L. et al, 2015;Arai et al, 2016). Earlier reports revealed that the upregulation of the Nrf2/HO-1 proteins has an anti-apoptosis role, and that the activation of Nrf2 could induce the expression of HO-1 to enhance the expression of Bcl-2 (Ma et al, 2015).…”
Section: ;mentioning
confidence: 99%